Durability characteristics of lightweight rubberized concrete. (10th November 2019) - Pham, Thong M.; Elchalakani, Mohamed; Hao, Hong; Lai, Jeffrey; Ameduri, Shaun; Tran, Tung M.
Highlights: Carbonation test results of rubberized concrete. Half-cell potential test results of rubberized concrete. Service life investigation of rubberized concrete. Estimated service life of 15% rubberized concrete exceeds 50 years. Effect of pretreatment methods on the characteristics of rubberized concrete. Abstract: This study experimentally investigates the durability characteristics of rubberized concrete up to 30% rubber content. The durability characteristics including the carbonation depth, standard potential, water absorption, and initial rate of absorption of rubberized concrete were investigated. The experimental results have shown that rubberized concrete absorbed more water than conventional concrete, and the water absorption increased with the rubber content. Therefore, rubberized concrete is more susceptible to water, chloride, and chemical attacks. The carbonation depth of rubberized concrete was also higher than that of the conventional concrete and it increased with the rubber contents, indicating more susceptibility to corrosion. Although the estimated service life of rubberized concrete is shorter than that of conventional concrete, with 15% rubber contents it exceeds 50 years according to fib CEB-FIP [1] and AS 3600 [2]. Rubberized concrete thus can be used for structural components with sufficient strength and adequate service life up to 15% rubber content. In addition, the pre-treatment methods with NaOH or water were found to have considerable effects on carbonation depth but marginal effects on the water absorption and standard potential of rubberized concrete.